2018
DOI: 10.1016/j.jalgebra.2018.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Monomial ideals with tiny squares

Abstract: Let I ⊂ K[x, y] be a monomial ideal. How small can µ(I 2 ) be in terms of µ(I)? It has been expected that the inequality µ(I 2 ) > µ(I) should hold whenever µ(I) ≥ 2. Here we disprove this expectation and provide a somewhat surprising answer to the above question.Theorem 1.1. For every integer m ≥ 5, there exists a monomial ideal I ⊂ K[x, y] such that µ(I) = m and µ(I 2 ) = 9.Moreover, this result is best possible for m ≥ 6.Theorem 1.2. Let I ⊂ K[x, y] be a monomial ideal. If µ(I) ≥ 6 then µ(I 2 ) ≥ 9.Here are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 4 publications
(9 reference statements)
1
30
0
Order By: Relevance
“…Note that this bound is no longer valid if I is not equigenerated. Indeed, for each m ≥ 6 there exists a monomial ideal in two variables such that |G(I)| = m and |G(I 2 )| = 9, see [4]. The next proposition is exactly Theorem 2.1 in [9], but we give an alternative proof.…”
Section: Connection To Freiman Idealsmentioning
confidence: 85%
“…Note that this bound is no longer valid if I is not equigenerated. Indeed, for each m ≥ 6 there exists a monomial ideal in two variables such that |G(I)| = m and |G(I 2 )| = 9, see [4]. The next proposition is exactly Theorem 2.1 in [9], but we give an alternative proof.…”
Section: Connection To Freiman Idealsmentioning
confidence: 85%
“…How small can jGðI i Þj be in terms of jGðIÞj? This question has been explored in [1] and [3]. We intuitively expect that the inequality jGðI 2 Þj > jGðIÞj should hold and that jGðI i Þj, i !…”
Section: Introductionmentioning
confidence: 99%
“…2, grows further whenever jGðIÞj ! 2: This expectation has been disproven in [1]: the authors construct a family of ideals in K½x, y for which jGðIÞj > jGðI 2 Þj:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption that I be equigenerated is essential. Indeed, in [4] it has been shown that for every integer m ≥ 6, there exists a monomial ideal I ⊂ K[x, y] such that µ(I) = m and µ(I 2 ) = 9.…”
Section: Introductionmentioning
confidence: 99%